Mechanism‐based approach using a biomarker response to evaluate tocilizumab subcutaneous injection in patients with rheumatoid arthritis with an inadequate response to synthetic DMARDs (MATSURI study). (12th October 2013) - Ohta, Shuji; Tsuru, Tomomi; Terao, Kimio; Mogi, Seiji; Suzaki, Midori; Shono, Eisuke; Ishida, Yoshimasa; Tarumi, Eriko; Imai, Masato
Abstract A multicenter, open‐label, dose‐escalation phase 1/2 study was undertaken to evaluate the optimal subcutaneous tocilizumab dose that would result in exposure comparable to the intravenous tocilizumab 8‐mg/kg approved dose in patients with rheumatoid arthritis. A pharmacokinetic and biomarker approach was used to estimate the clinical optimal dose regimen of subcutaneous tocilizumab. Safety and efficacy of subcutaneous tocilizumab were assessed as secondary end points. Patients received subcutaneous tocilizumab at 81 mg every 2 weeks (q2w) (n = 8), 162 mg q2w (n = 12), or 162 mg weekly (qw) (n = 12) for 24 weeks. 88% of 162‐mg q2w patients and 100% of 162‐mg qw patients maintained mean serum trough tocilizumab concentrations of ≥1 µg/mL, and had exposure comparable with the approved intravenous tocilizumab dose of 8 mg/kg; this resulted in normalized C‐reactive protein levels and improvement in ACR20/50/70 responses. The most common adverse events were abnormal laboratory results, which were mild in severity. Anti‐tocilizumab antibodies were detected in a few patients in the 81‐mg q2w and 162‐mg qw groups. In conclusion, coupled with efficacy and tolerability results, the appropriate dose of subcutaneous tocilizumab was determined to be 162 mg q2w for Japanese patients.